Pencegahan hipertensi dan penebalan dinding aorta dengan pemberian kecambah kacang hijau (Phaseolus radiatus (L)) pada tikus putih Sprague Dawley - Novian Swasono Hadi; Arta Farmawati; Ahmad Ghozali (Jurnal Gizi Klinik Indonesia, 2016)
Background: Lifestyle changes with high-fat food consumption is one of the factors the risks of cardiovascular diseases like of coronary heart disease and atherosclerosis. A healthy diet and a balanced diet and consume foods that contain lots of antioxidants is one of the effective ways to prevent hyperlipidemia. Mung bean sprouts have properties that neutralize free radicals cause Hyperlipidemia and cardiovascular diseases because it is an antioxidant compound.Objective: The aim of this study was to determinate the effect of mung bean sprouts (Phaseolus radiatus (L)) to blood pressure and histopathology aorta of Sprague-Dawley male rats.Method: The type of study was experimental research using pre-post test controlled group design for blood pressure variable and post test only controlled group design histopathology aorta. The thirty-five of Sprague-Dawley male rats was eight weeks divided into 5 groups. The first group was given standard diet, group 2 was given a hight fat diet, the third group was given a high-fat diet and mung bean sprout 0,67 gram, group 4 was given a high-fat diet and mung bean 1,34 gram, and group 5 was given a high-fat diet and vitamin E doses of 23 IU.Results: Result of this study showed that after 4 weeks of treatment, increased in blood pressure systole in the given of  high fat diet higher than group who were given a high fat diet and mung bean sprout and also on group who were given high fat diet and vitamin E, but there is no difference effect a decrease in blood pressure between the provision of mung bean sprouts and vitamin E (p>0,05). Statistical analysis to thick the wall the aorta show the similarity meaningful in all the treatment group, it can be said that overall thick the wall the aorta in this research is not different.Conclusion: A dose of mung bean sprout 0,67 g is optimal doses in preventing a rise in blood pressure and prevent alterations histopathology Sprague-Dawley male rats.